2024
DOI: 10.1027/1015-5759/a000729
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Dutch Version of the Plymouth Sensory Imagery Questionnaire

Abstract: Abstract. Mental imagery plays an important role in the onset and maintenance of psychological disorders as well as their treatment. Therefore, a reliable and valid measure of mental imagery is essential. Andrade and colleagues (2014) developed the Plymouth Sensory Imagery Questionnaire (PsiQ), which contains 35 items (long version) or 21 items (shortened version) measuring the vividness of mental imagery in seven different modalities: vision, sound, smell, taste, touch, bodily sensation, and emotion. Andrade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…However, these interpretations of cultural differences in taste, smell, and sound are only tentative and will be veri ed in the future. Furthermore, Psi-Q has already been translated into Spanish (Pérez-Fabello & Campos, 2020) and Dutch (Woelk et al, 2022), and comparative studies with more diverse cultures could be conducted.…”
Section: Cultural Comparison Of Multisensory Imagery Abilitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, these interpretations of cultural differences in taste, smell, and sound are only tentative and will be veri ed in the future. Furthermore, Psi-Q has already been translated into Spanish (Pérez-Fabello & Campos, 2020) and Dutch (Woelk et al, 2022), and comparative studies with more diverse cultures could be conducted.…”
Section: Cultural Comparison Of Multisensory Imagery Abilitymentioning
confidence: 99%
“…Furthermore, by translating the Psi-Q, which is already in use in various countries, we can examine cultural differences in multisensory imagery. Although a Spanish version (Pérez-Fabello & Campos, 2020) and a Dutch version (Woelk et al, 2022) of this scale have already been developed, to our knowledge there are no studies examining cultural differences in multisensory imagery ability. It is not a country comparison, but Talamini et al (2022) asked musicians and non-musicians to complete questionnaires on visual and auditory imagery abilities, and found that musicians had higher auditory imagery abilities, while there was no difference in visual imagery abilities.…”
Section: Scales Of Each Sensory Imagery Ability Japanese Versions And...mentioning
confidence: 99%
“…Nevertheless, these interpretations of cultural differences particularly in sound, smell, and taste are only tentative and must be verified in the future. Furthermore, the Psi-Q has already been translated into Spanish (Pérez-Fabello and Campos, 2020) and Dutch (Woelk et al, 2022), and comparative studies with more diverse cultures should be conducted.…”
Section: Cultural Comparison Of Multisensory Imagery Abilitymentioning
confidence: 99%
“…Although we were able to develop a Japanese version of the Psi-Q and validate its validity and reliability in this study, several limitations must be mentioned. First, as with the original and translated versions (Andrade et al, 2014;Pérez-Fabello and Campos, 2020;Woelk et al, 2022), the short version was created by reducing items from the long version, and some concerns have been noted with this method of creation (c.f., Aquino et al, 2018), as the same item may be regarded differently in the long and short versions. Second, although we made cultural comparisons, these are exploratory results, and based on the results obtained in this study, hypotheses need to be developed and factors that cause cultural differences in multisensory mental imagery abilities need to be further explored.…”
Section: Limitation and Future Directionmentioning
confidence: 99%
See 1 more Smart Citation